Six Sigma Implementation in Connector and Terminals Manufacturing Company : A Case Study - Hendi Herlambang (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
This research was conducted at an electronic component company located in Bekasi, Indonesia. Quality is a characteristic of this company, with the company's mission, one of which is eliminating customer claims. The application of the Six Sigma DMAIC method is expected to be used as a guideline for making durable product quality and reducing the high variation in the manufacturing process for bullet type products. This study aims to determine the variables of the factors that can affect the retention force value of bullet type terminal products, using the Taguchi method experiment. The research results with the Taguchi method experiment found that three variables affect the product retention force value, namely the largest outer diameter dimension, the most significant input diameter size dimension, and the smallest length position size dimension. After monitoring and data collection on the retention force dimension, it was found that the overall Cp process capability was 3.38, and Cpk was 1.58, so it could be said that the machine performance was excellent and stable.